Navigating Complexity: Enhancing Infrastructure Megaproject Performance Through Effective Alliance Management Capability - Xiaoyan Chen; Daoan Fan; Yan Liu; Xinyue Zhang (Buildings)
While extensive research has delved into the impact of management strategies on project outcomes, the specific influence of alliance management on infrastructure megaprojects remains less explored. This study delves into the relationship between alliance management capability and performance in the context of infrastructure megaprojects. Central to our investigation is the hypothesis that collaborative conflict management mediates this relationship, with leader–member exchange playing a moderating role. Based on 205 surveys collected from 13 megaprojects in China, regression analysis and bootstrapping methods were used to test the research hypotheses. The findings reveal a positive correlation between alliance management capability and infrastructure megaproject performance, mediated by collaborative conflict management. Significantly, leader–member exchange acts as a moderator in the alliance management capability–collaborative conflict management nexus. These insights underscore the pivotal role of alliance management capability in elevating project performance, meriting increased attention in future empirical research. By shedding light on the mediating and moderating mechanisms at play, this paper unravels the complexities of how alliance management capability impacts project performance, offering practical guidance for industry practitioners.